Chapter 12 Beating the Border - Soberon, Lennart; Smets, Kevin (Taylor & Francis, 2025)
This edited volume explores the idea of Europe through a focus on its margins. The chapters in the volume inquire critically into the relations and tensions inherent in divisions between the Global North and the Global South as well as internal regional differentiation within Europe itself. In doing so, the volume stresses the need to consider Europe from critical interdisciplinary perspectives, highlighting historical and contemporary issues of racism and colonialism. While recent discussions of migration into ‘Fortress Europe’ seem to assume that Europe has clearly demarcated geographic, political and cultural boundaries, this book argues that the reality is more complex. The book explores margins conceptually and positions margins and centres as open to negotiation and contestation and characterized by ambiguity. As such, margins can be contextualized in relation to hierarchies within Europe, with different processes involved in creating boundaries and borders between different kinds of Europes and Europeans. Deploying case studies from different places, such as Iceland, Italy, Poland, Spain, Turkey, the UK, Romania, Cyprus, Greece, Sicily, European colonies in the Caribbean and the former Yugoslavia, the contributors analyse how different geopolitical hierarchies intersect with racialized subject positions of diverse people living in Europe, while also exploring issues of gender, class, sexuality, religion and nationality. Some chapters draw attention to the fortification of Europe’s ‘borderland,’ while others focus on internal hierarchies within Europe, critiquing the meaning of spatial boundaries in an increasingly digitalized Europe. In doing so, the chapters interrogate the hierarchies at play in the processes of being and becoming ‘European’ and the ongoing impacts of race and colonialism. This timely and thought-provoking collection will be of considerable significance to those in the humanities and social sciences with an interest in Europe.